STATUS OF INDIGENOUS OREOCHROMIS AND OTHER OREOCHROMINI SPECIES USING DNA BARCODING - Mojekwu, T. O; Cunningham, M. J.; Hoareau, T. B. (Nigerian Journal of Fisheries, 2025)
Nile tilapia (Oreochromis niloticus) and their hybrids has been used across the world for aquaculture. However, it can represent a threat to the genetic integrity of wild populations, as in the case of the Mozambique tilapia (Oreochromis mossambicus) in Southern Africa. Most of the available genetic data on Oreochromis comes from unknown wild source. DNA barcoding approach using mtDNA COI sequences was applied to improve the knowledge on biodiversity of the Oreochromis genus. The objectives include: assessing the genetic diversity of the tribe Oreochromini and test its monophyly; evaluate the genetic status of both O. mossambicus and O. niloticus focussing on the diversity of wild populations, and evaluating the genetic status of the genus Oreochromis within the tribe Oreochromini. The methodology involved retrieving mtDNA COI sequences from publicly available databases (BOLD and NCBI) and generating new sequencing on 81 specimens from 43 locations of the native ranges and 13 specimens from a hatchery. Maximum likelihood (ML) algorithm was used to analyse the combined sequences (532 bp fragment; N=560) in MEGA version 7.0.14. Results revealed clues of mtDNA introgression and polyphyly of species of the tribe Oreochromini. Cryptic diversity in wild Oreochromis populations, with multiple lineages of both O. mossambicus and O. niloticus. Oreochromis genus status need to be revisited based on the relationship between O. aureus and Sarotherodon with genetics distance ranging from 0.05 and 0.07. The overal average genetic distance in Oreochromis was 0.06. However, the genetic distances between O. mossambicus and O. niloticus was 0.06 while the distances between these species and O. aureus were 0.08 and 0.09 respectively. These results highlight the importance of revising the taxonomy of the tribe, assessing the phylogenetic relationships between taxa, and creating reference barcoding library that serves as an important molecular resource. : , , , ,